2017
DOI: 10.1016/j.cmi.2016.12.022
|View full text |Cite
|
Sign up to set email alerts
|

Role of inoculum and mutant frequency on fosfomycin MIC discrepancies by agar dilution and broth microdilution methods in Enterobacteriaceae

Abstract: The higher inoculum used in the microdilution method enriched the initial inoculum with resistant subpopulations and could partially explain the fosfomycin MIC discrepancies with respect to the agar dilution method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 21 publications
1
29
1
Order By: Relevance
“…The degree of comparability varied among species, and the differences tended to be one 2-fold dilution higher in broth, although there were examples of multiple fold increases. Ballestero-Tellez showed 86.4% categorical agreement when testing 81 E. coli isolates in broth microdilution with G-6-P compared to reference agar dilution and 51.1% categorical agreement for 139 K. pneumoniae isolates (22).…”
Section: Resultsmentioning
confidence: 94%
“…The degree of comparability varied among species, and the differences tended to be one 2-fold dilution higher in broth, although there were examples of multiple fold increases. Ballestero-Tellez showed 86.4% categorical agreement when testing 81 E. coli isolates in broth microdilution with G-6-P compared to reference agar dilution and 51.1% categorical agreement for 139 K. pneumoniae isolates (22).…”
Section: Resultsmentioning
confidence: 94%
“…Concerning the presence of double deletions, the ΔcyaA ΔglpT and ⌬ptsI ΔcyaA strains showed the highest reductions in the maximal growth rate in MH broth. We previously showed that FOS MIC determination may not be an accurate predictor of FOS efficacy (25,38). Susceptibility testing gives a measure of growth inhibition (MIC) under specific in vitro conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Fosfomycin maintains in vitro activity against the vast majority of E. coli clinical strains, with reported susceptibility rates ranging between 94 and 99% (26)(27)(28). It is well acknowledged that resistance to fosfomycin can readily emerge spontaneously in vitro when conducting susceptibility testing (13,29,30). As fosfomycin use increases, the demand for susceptibility testing of this agent is expected to rise.…”
Section: Discussionmentioning
confidence: 99%